Effect of plant growth regulators (PGRs) on flowering, fruit-set and yield of cashew var. Jhargram-1 - Singh, L.S.; Pariari, A. (Journal of Plantation Crops, 2012)
Four commonly used plant growth regulators such as NAA, 2,4-D, ethrel and GA3 were sprayed (single or double) at panicle initiation and peak flowering stage in cashew var. Jhargram-1. Results showed that spraying of ethrel 50 ppm twice, significantly produced maximum number of panicle per square meter. Spraying PGRs except 2,4-D had beneficial effect for most of the economic traits of the plants. NAA 100 ppm double spray was found to be the most effective to increase number of perfect flowers, fruit retention, nuts per square meter and yield per square meter. The study also revealed that spraying of GA3 50 ppm (both single and double spray) significantly produced more number of staminate flowers. Duration of flowering more than 60 days was recorded with double spray of GA3 50 ppm, NAA 100 ppm and GA3 100 ppm.